2016
DOI: 10.1177/0163278715625738
|View full text |Cite
|
Sign up to set email alerts
|

Survey Methods to Optimize Response Rate in the National Dental Practice–Based Research Network

Abstract: Surveys of health professionals typically have low response rates, and these rates have been decreasing in the recent years. We report on the methods used in a successful survey of dentist members of the National Dental Practice–Based Research Network. The objectives were to quantify the (1) increase in response rate associated with successive survey methods, (2) time to completion with each successive step, (3) contribution from the final method and personal contact, and (4) differences in response rate and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 45 publications
3
58
3
1
Order By: Relevance
“…Apropos to the current study, Funkhouser et al 18 recently reported achievement of an 87% response rate in a survey of 1,716 eligible dentists affiliated with the National Dental Practice-Based Research Network (NDPBRN) through application of rigorous recruitment using a mixed mode strategy. The authors noted that the robust participation rate was possibly attributable to some degree to the targeted dental group who projected a pro-active interest in research by virtue of their membership in the NDPBRN.…”
Section: Discussionmentioning
confidence: 94%
“…Apropos to the current study, Funkhouser et al 18 recently reported achievement of an 87% response rate in a survey of 1,716 eligible dentists affiliated with the National Dental Practice-Based Research Network (NDPBRN) through application of rigorous recruitment using a mixed mode strategy. The authors noted that the robust participation rate was possibly attributable to some degree to the targeted dental group who projected a pro-active interest in research by virtue of their membership in the NDPBRN.…”
Section: Discussionmentioning
confidence: 94%
“…57 Useful resources include http://www.qualtrics.com/blog/how-to-increase-online-survey-response-rates/ and http://socialnorms.org/what-is-an-acceptable-survey-response-rate/.…”
Section: Advantages and Disadvantages Of Surveysmentioning
confidence: 99%
“…A limitation of the study is the low response rate. This is fairly typical of surveys of health professionals and has been further reinforced by response rates showing a decrease over recent years (34). Although the response rate recorded for this survey was less than 2% of all the members of AGD, it is unclear how many of its members read the online newsletter which included details about participating in the survey.…”
Section: Limitation Of the Studymentioning
confidence: 69%